IMPLEMENTASI SISTEM INFORMASI STOCK OPNAME WAREHOUSE PADA PD. SINAR MAS (HAKASIMA) JAMBI: Information System, Warehouse, PD. Sinar Mas (Hakasima) - Mulyati, Sri; Mulyadi; Natalia, Messy (JURNAL AKADEMIKA, 2023)
Warehouse is one of the supporting elements that have a vital role in a company. Therefore, a small error in data storage or stock counting, can result in paralyzing a company and sometimes even creating a company. According to the author's assessment, the data storage system and stock counting in PD. Sinar Mas (Hakasima) Jambi, is still far from being effective. This is because there are still many manual records found by the author from the PD warehouse staff. Sinar Mas (Hakashima).